The droxel: A universal parametric construction component. (1st January 2022) - Latteur, Pierre; Fascetti, Alessandro; Goessens, Sébastien
Highlights: Droxels are suitable for both robotic operations and homemade construction. Droxels can materialize any 3D surface or volume with good structural stability and an easy interlocking. Droxels allow for fast and easy construction with polymers, timber and concrete. Polymers allow filling the droxels with water, insulation, sand, recycled ballast. Abstract: Recent disruptive advancements in the fields of robotics, advanced manufacturing and parametric design will transform the construction industry in the next decades. In this article, we take advantage of the possibilities offered by these technologies to develop a new family of universal construction components that we called "droxels". They bring together many characteristics that make them suitable for both robotic operations and traditional construction: they make it possible to materialize any 3D surface or volume with good structural stability, they allow an easy interlocking with a large laying tolerance, and they avoid scaffolding thanks to carefully chosen intermediate construction phases. Possible materials are polymers, timber, and concrete. In particular, polymers allow filling the droxels with water, or insulation, or sand, or recycled ballast. However, droxels have a complex geometry defined by eight parameters. The aim of this paper is to perform a comprehensive sensitivity analysis to characterize the influence of each of them on the characteristics of droxels and droxel-based engineering structures, such as the quality of interlocking or the feasibility of cantilevers. The methodology consists of an analytical and geometrical approach based on parametric design tools developed in Grasshopper. Finally, the results of the parametric study confirm that droxels can be used for many practical applications and a synthesis is given in order to guide the designer in the choice of the geometrical parameters, according to the characteristics of the structure and the construction process.